2011
DOI: 10.2147/tcrm.s16643
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and clinical overview of cloperastine in treatment of cough

Abstract: Abstract:Cough constitutes an impressive expression of the normal defense mechanisms of the respiratory system. Productive cough associated with catarrh is an important protective system for the lung because it favors the upward movement of secretions and foreign bodies to the larynx and mouth. Cough may also appear without bronchial secretions, as dry cough, which may be persistent when inflammatory disease is chronic or when, in the early stages of respiratory disease, bronchial secretions are not yet fluid.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Cloperastine ( Figure 5 , top left) is a cough-suppressant which acts to suppress the CNS cough center ( 56 ). Discovered in studies of derivatives of the first-generation antihistamine diphenhydramine ( Figure 5 , top right) ( 57 ), it also possesses antihistaminic activity. The SEA study suggested and experimentally confirmed binding of cloperastine to the sigma receptor, and noted that this could explain its antitussive activity, based on the known relationship of activity at the sigma receptor type 1 to cough ( 58 ).…”
Section: Resultsmentioning
confidence: 99%
“…Cloperastine ( Figure 5 , top left) is a cough-suppressant which acts to suppress the CNS cough center ( 56 ). Discovered in studies of derivatives of the first-generation antihistamine diphenhydramine ( Figure 5 , top right) ( 57 ), it also possesses antihistaminic activity. The SEA study suggested and experimentally confirmed binding of cloperastine to the sigma receptor, and noted that this could explain its antitussive activity, based on the known relationship of activity at the sigma receptor type 1 to cough ( 58 ).…”
Section: Resultsmentioning
confidence: 99%
“…The regular clinical dose of cloperastine as a cough suppressant (10–20 mg three times daily for adults) is calculated to be approximately 3 µM. However, chronic toxicity tests performed in rats treated for 3 months with cloperastine hydrochloride at 15 mg/kg (45 µM) or 45 mg/kg (135 µM), and in dogs treated for 3 months with cloperastine hydrochloride at 20 mg/kg (60 µM) revealed no particular symptomatology or changes in hematochemical, hematological, or urinary parameters as compared to control animals and baseline values 10 . Thus, given the priority of cancer therapy, application of cloperastine to kill cisplatin-resistant cancer cells would be well within the scope of clinical testing.…”
Section: Discussionmentioning
confidence: 99%
“…4B, Translation), and sigma receptors such as Haloperidol 23 and Compound PB28 24 (Fig. 4A Nsp6 and Orf9c), Melperone, Cloperastine, 25 and Clemastine (Fig. 4B, Protein Processing), and the female hormone progesterone (Fig.…”
Section: Molecular Description Of Coronavirus Envelopementioning
confidence: 99%